2007
DOI: 10.1518/001872007x230154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Information Source, Pedigree, and Reliability on Operator Interaction With Decision Support Systems

Abstract: The results provide a reference point for deriving indices of "optimal" user interaction with decision aids and for developing frameworks of trust in decision support systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 25 publications
7
95
3
Order By: Relevance
“… If an automated system makes an error, then it is broken  If an automated system makes a mistake, then it is completely useless  Correctly-functioning automated systems are perfectly reliable  Only faulty automated systems provide imperfect results Madhavan and Wiegmann (2007) argued that initial biases related to perceptions of automation are likely to be implicit in nature (pp. 775).…”
Section: All-or-none Belief Itemsmentioning
confidence: 99%
See 2 more Smart Citations
“… If an automated system makes an error, then it is broken  If an automated system makes a mistake, then it is completely useless  Correctly-functioning automated systems are perfectly reliable  Only faulty automated systems provide imperfect results Madhavan and Wiegmann (2007) argued that initial biases related to perceptions of automation are likely to be implicit in nature (pp. 775).…”
Section: All-or-none Belief Itemsmentioning
confidence: 99%
“…Biases toward automation may be partly implicit in nature (Madhavan and Wiegmann, 2007). Thus, an IAT was used to assess participants' implicit attitudes toward automation.…”
Section: Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They called this effect cognitive anchoring. Studies have also shown that people generally trust in automated systems and consider them more reliable than manual operation ("perfect automation schema"; [24]) or other people [18,31,36]. Those positive attitudes may result a higher tendency to rely on the aid and comply with its suggestions, i.e.…”
Section: Aims Of the Study And Hypothesesmentioning
confidence: 99%
“…These applications of intelligent automated agent systems have fundamentally changed the relationship between humans and automation. The role of human operators has transformed from a main controller to a teammate sharing control with automated agents [32]. However, when automated agents become more like a 'partners' rather than just tools [14], how humans calibrate appropriate trust relations while interacting with intelligent agent systems becomes an important but challenging question.…”
Section: Introductionmentioning
confidence: 99%